2023
DOI: 10.1002/gch2.202200162
|View full text |Cite
|
Sign up to set email alerts
|

Big Things, Small Packages: An Update on Microalgae as Sustainable Sources of Nutraceutical Peptides for Promoting Cardiovascular Health

Abstract: In 2017, a review of microalgae protein‐derived bioactive peptides relevant in cardiovascular disease (CVD) management was published. Given the rapid evolution of the field, an update is needed to illumininate recent developments and proffer future suggestions. In this review, the scientific literature (2018–2022) is mined for that purpose and the relevant properties of the identified peptides related to CVD are discussed. The challenges and prospects for microalgae peptides are similarly discussed. Since 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…AIA is a well-known experimental model of polyarthritis that resembles RA and exhibits many clinical features, including limb edema, joint inflammation, synovial hyperplasia, and cartilage damage [36]. Natural marine products, particularly bioactive peptides, possess potential health benefits [37]. In this study, we observed that the major marine animals-derived peptides, such as those obtained from A. japonicus, A. leucoprocta, M. aeglefinus, P. esculenta and R. esculentum, have assisted in alleviating arthritis in mice to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…AIA is a well-known experimental model of polyarthritis that resembles RA and exhibits many clinical features, including limb edema, joint inflammation, synovial hyperplasia, and cartilage damage [36]. Natural marine products, particularly bioactive peptides, possess potential health benefits [37]. In this study, we observed that the major marine animals-derived peptides, such as those obtained from A. japonicus, A. leucoprocta, M. aeglefinus, P. esculenta and R. esculentum, have assisted in alleviating arthritis in mice to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to separate peptide fragments since they all have different sizes, charges, and physicochemical properties [15]. Utilising chromatography methods, biologically active peptides are usually segregated based on their molecular size, ionic charge, and differential affinity for the stationary and mobile phases [56,57]. To acquire desired peptides, those approaches remove the harmful residue and unwanted solvents.…”
Section: Purification Of Bioactive Peptidementioning
confidence: 99%